Bolavoli : Latihan Ball Drop Drill untuk Meningkatkan Keterampilan Pasing Bawah - Sari, Eka Novita; Irwanto, Edi; Triaiditya, Bayu Septa Martaviano; Santoso, Danang Ari (MAN Insan Cendekia Jambi, 2024)
This research aims to determine the effect of ball drop drill training on improving the bottom passing skills of female volleyball athletes at SMAN 1 Tegaldlimo. This research uses experimental methods. The sample in this research consisted of 8 students. The technique for collecting data on fitting skills uses AAHPERD TEST tests and measurements. The data analysis technique uses SPSS 25. The results of the research show that there is a significant increase in bottom fitting skills by using ball drop drill training at 0.001 < 0.05. This means that this exercise can be used to improve volleyball bottom passing skills.